Stage management - Stern, Lawrence 1935-; Gold, Jill (New York Routledge, 2017)
The book offers readers a practical manual on how to stage manage in all theatre environments. Revered as the authoritative resource for stage management, this text is rich with practical resources, including checklists, diagrams, examples, forms and step-by-step directions. In addition to sharing his own expertise, Stern has gathered practical advice from working stage managers of Broadway, off-Broadway, touring companies, regional, community, and 99-seat Equity waiver theaters. In its 11th edition, the book is now fully in color and updated to include new information on Equity contracts, social media applications in stage management, and working with high school productions.
Making Things Run Smoothly -- Characteristics of a Good Stage Manager -- Getting the Play and Understanding It -- Scheduling and Company Rules -- Getting Acquainted with your Theatre -- Expediting Auditions and Readings -- Budgeting -- Rehearsal Procedures -- Keeping the Cast On Time -- Department Management and Property Management -- Supervision of Shifts -- Running the Technical Rehearsal -- Running the Show -- Working with the House Manager -- Keeping the Show in Hand -- Closing and Moving/Touring -- Fire/Evacuation -- Working with Unions -- Organizing Information -- Correspondence -- Getting a Job -- Appendices.
"A Focal Press Book" -- Cover.
Includes bibliographical references and index.
Keywords: Stage management